South African Taxpayers Perceptions towards E-Filing - Baneng Naape (Journal of Economics and Financial Analysis, 2022)
The study has two parts: the first part studies how South African taxpayers felt about e-filing, and the second part analyses how e-filing affected tax compliance. We use self-structured questionnaires to collect data from about 151 South African taxpayers, and we analyze them using binary logistic regression. The study finds that online tax registration and auto-assessment has a negative relationship with tax compliance in South Africa, while online payment methods, difficulty in tax evasion, and higher educational attainment have a positive association with tax compliance. The study also finds that the extent to which the e-filing system encourages taxpayers to become compliant has a positive and statistically significant relationship with tax compliance. Overall, the study suggests that the development of e-filing has a positive impact on taxpayers' perceptions in South Africa and significantly increases voluntary tax compliance. To maximize the benefits of e-filing, it is important to ensure that taxpayers have access to the necessary technology and knowledge to use it effectively.
Keywords: H24; C51; 330; Tax Compliance; Information Technology; Binary Logistic Regression; E-Filing